Quasi-static tensile properties of the Cranial Cruciate Ligament (CrCL) in adult cattle: towards the design of a prosthetic CrCL. (March 2018) - Diotalevi, Lucien; Petit, Yvan; Brailovski, Vladimir; Nichols, Sylvain; Marchionatti, Emma; Wagnac, Éric
Abstract: Mechanical properties of the Cranial Cruciate Ligament (CrCL) in adult cattle are not well documented and protocols used in the literature focus on testing a full femur-CrCL-tibia complex rather than an isolated CrCL. The aim of this study was to assess a wider range of tensile properties of the CrCL along its anatomic axis with experimental measurements of the global elongation, displacement and strain fields, in order to provide guidelines for the design of CrCL prosthetic surrogates. Fourteen bovine CrCL were harvested from seven mature cows (5.1 ± 1.3 years) weighing 631 ± 90 kg. The mean CrCL length was 41.4 ± 1.5 mm and its mean cross-section was 103.9 ± 23.8 mm 2 . Pre-conditioning was achieved with 30 cycles of loading from 30 to 200 N at a strain rate of 0.02 s −1 . Specimens were then loaded to failure at the same strain rate. The following results were obtained: the mean ultimate tensile load (UTL) 4372 ± 1485 N and the median [quartiles] maximal global elongation 19.3 [17.8; 21.4] %. At first physical signs of tearing, the mean load was 3315 ± 1336 N and mean elongation 13.5 ± 4.9%. The mean absorbed energy at failure was 5.23 ± 2.08 MJ.m m −3 and the mean stiffness at various levels of elongation was: 220 ± 195 N.% −1 (5%), 285 ± 162 N.% −1 (10%), 239 ± 200 N.% −1 (15%), 146 ± 59 N.% −1 (20%), 153 ± 136 N.% −1 (25%). None of these properties were related to the bovine weight, age and side of the body (p > 0.05). An ideal prosthetic surrogate should then follow these sets of properties and the experimental data suggest that the in-vivo maximal elongation is below 13.5%. Graphical abstract: fx1 Highlights: A new methodology is proposed for the mechanical assessment of ligaments in cattle. Displacement and strain fields measurements on bovine CrCLs are carried out. Guidelines are provided for the design of bovine CrCL surrogates.